Th1 and Th2 types cytokine production by the activated peripheral blood mononuclear cells (PBMCs) from atopic dermatitis patients – relationship to the clinical parameters and Staphylococcus aureus skin colonization - Kędzierska, Anna; Kapińska-Mrowiecka, Monika; Czubak-Macugowska, Marzena; Kaszuba-Zwoińska, Jolanta; Pryjma, Juliusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Recent studies have shown that local up-regulation of Th2 cytokines and handicap of IFN-γ and TNF-α production under inflammatory conditions increase susceptibility of AD skin to microorganism. The aim of this study was to determine whether different density of S. aureus colonizing two different sites (lesional and non-lesional skin areas), and clinical condition of AD patients have any impact on Th1 and Th2 cytokine profiles. Cell culture supernatants of peripheral blood mononuclear cells from AD patients and control group were collected following SEB stimulation. The number of bacteria was determined by colony forming unit method. IFN-γ, TNF-a, IL-2, IL-4, IL-5, and IL-10 was evaluated using specific ELISA and Human Th1/Th2 Cytokine Cytometric Bead Array. The patients were characterized by age, sex, severity scoring of AD, and serum eosinophil cationic protein. Twenty three (62.2%) among 37 of AD patients were positive for S. aureus cultured from both sites of the skin. SEB-stimulated PBMC s from patients with high density of S. aureus on involved (log>7.14) and uninvolved (log>5.48) skin had significantly reduced amount of IFN-γ and TNF-α production than normal non-AD individuals (P<0.001 and P<0.05, respectively). Although the production of IFN-γ and TNF-α by AD patients was significantly lower than healthy controls, the production of IL-4 and IL-5 was not increased in SEB-stimulated cultures. The severity scores, but not the density of S. aureus , negatively correlated to IFN-γ production (P<0.01). S. aureus skin colonization in AD patients although correlated to the severity of symptoms have an impact on patient’s T-cell responsiveness to SEB.